Incidence and Characterization of Concealed Cardiac Amyloidosis Among Unselected Elderly Patients Undergoing Post-mortem Examination - Porcari, Aldostefano; Bussani, Rossana; Merlo, Marco; Varrà, Guerino Giuseppe; Pagura, Linda; Rozze, Davide; Sinagra, Gianfranco (Frontiers in Cardiovascular Medicine, 2021)
Background The prevalence of cardiac amyloidosis (CA) is unknown. Aims and Methods We sought to a) determine the prevalence of CA in unselected patients ≥75 years undergoing autopsy, b) characterize cardiological profiles of CA and non-CA patients by providing clinical-histological correlations, and c) compare their cardiological profiles. After dedicated staining, the localization (interstitial or vascular) and the distribution (non-diffuse or diffuse) of amyloid deposition were analysed. Cardiological data at last evaluation were retrospectively assessed for the presence of CA red-flags. Results CA (50% light chains, 50% transthyretin) was found in 43% (n=24/56) of the autopsied hearts. Atria were involved in 96% of cases. Amyloid localized both at the perivascular and interstitial levels (95.5% and 85%, respectively) with a slightly predominant nondiffuse distribution (58% of cases). Compared to the other patients, CA patients had a more frequent history of heart failure (HF) (79% vs 47%, p=0.014), advanced NYHA functional class (III-IV 25% vs 6%, p=0.047), atrial fibrillation (68% vs 36%, p=0.019), discrepancy between QRS voltage and left ventricular (LV) thickness (70% vs 12%, p<0.001), thicker LV walls (15 mm vs 11 mm, p<0.001), enlarged left atrium (49 mm vs 42 mm, p=0.019) and restrictive filling pattern (56% vs 19%, p=0.020). The presence of right ventricular amyloidosis seemed to identify hearts with a higher amyloid burden. Among the CA patients, >30% had ≥3 echocardiographic red-flags of disease. Conclusion CA can be found in 43% of autopsied hearts from patients ≥75 years old, especially in patients with HF, LV hypertrophy and atrial fibrillation.